Teachers’ Professional Attitudes towards Inclusive Education - Silvia Barnová; Mária Kožuchová; Slávka Krásna; Róbert Osaďan (Emerging Science Journal, 2022)
In the study, an overview of the current situation in the field of inclusive education in Slovakia is presented. Since teachers’ attitudes towards inclusive education are among the key determinants of the success or failure of SEN students’ inclusion in mainstream schools, the main objective of the study was to investigate them in the context of implementing the new Strategy for Inclusive Education in Slovakia. In this quantitative study, Mahat [1] "The Multidimensional Attitudes Toward Inclusive Education Scale (MATIES)" was used and three components of teachers’ attitudes – cognitive, affective, and behavioral – were examined by means of univariate, bivariate, and multivariate methods of statistical analysis. As the aging of the teaching population is an issue in Slovakia, age-related peculiarities were focused on in the study. The findings revealed statistically significant differences in the affective and behavioral components between the two examined age-groups of teachers. Since no extensive study has been focused on teachers’ attitudes towards replacing school integration by school inclusion in Slovakia, the proposed study aims to fill the gap and provide unique data useful in the process of changing traditional schools into inclusive ones. The obtained results also point to the importance of considering teachers’ attitudes towards any changes to be introduced. Doi: 10.28991/ESJ-2022-SIED-02 Full Text: PDF